The synergistic effect of corporate social responsibility and ESG disclosure on green innovation: evidence from least developed countries - Murad Baqis Hasan; Ruchita Verma; Dhanraj Sharma; Ahmed Alaqel (Cogent Business & Management, 2024)
Existing literature frequently indicates a positive relationship between corporate social responsibility (CSR) and green innovation (GI), yet findings are not definitive. Furthermore, the potential moderating influence of environmental, social, and governance (ESG) disclosure has not received adequate attention. Therefore, this study aims to explore the moderating role of ESG disclosure in the relationship between CSR and GI among manufacturing SMEs in least developed countries, such as Yemen. To this end, data was collected from 227 Yemeni SME managers/owners and analyzed using SEM-PLS via SmartPLS. The results revealed a positive relationship between CSR and GI. Importantly, ESG disclosure moderates the CSR-GI relationship. These findings have theoretical and practical implications, which are discussed alongside suggestions for future research directions.
Keywords: 650; Corporate social responsibility; green innovation; esg disclosure; SMEs; least developed countries